The Role of Digital Technologies in Digital Transformation of Small Businesses : Experiences of Business Owners in Daily Operations, Customer Interaction, Competitiveness and Practical Challenges - Shahid, Nusrat Binta (My University, 2026)
This study explores the experiences of small business owners and their management of digital transformation in the course of their daily business operations with a view to gaining insight into the process of digital transformation particularly focusing on customer interaction, operational effectiveness, competitiveness, and the realities of implementing new digital technologies. Small business owners' experiences of digital transformation have become increasingly significant as digital technology plays a central role in their communication with customers, business operations, and the level of competition. To address the research question, a qualitative research approach has been undertaken and supported by the TOE framework. Data has been collected through semi-structured interviews with 5 owners of small businesses operating in service and retail oriented sectors (salons, online retail, restaurant, jewelry business and cake shop) which was then analyzed using thematic analysis. The research concluded that small businesses adopt easy- to use digital technologies such as social media platforms, online booking systems, digital payment, communication tool and delivery platform which enable better communication with customers, provide business exposure and improve operational efficiency and competitiveness. The results also indicated that in small businesses, digital transformation process is viewed more as an evolutionary and adaptable process than a formalized strategy and owners have confronted some challenges such as lack of finance and technical skills, time constraints, lack of integration, the never-ending learning and adaptation requirements.
Keywords: digitalisation; enterprises; innovations; customer experience; small enterprises; business; social media; technology; information technology; technological development; Artificial Intelligence and Data Engineering; Master’s Programme in Strategic Business Development